Mechanical behaviour of extremely tough TZP bioceramics. (February 2019) - Kern, Frank; Reveron, Helen; Chevalier, Jérôme; Gadow, Rainer
Abstract: Tetragonal Zirconia Polycrystals (TZP) is attractive for structural biomedical applications because of their excellent mechanical properties at room-temperature, which include high strength, fracture toughness and wear resistance. In this work, zirconia stabilized with Y or Yb or Yb+Nd, all containing 0.5 vol.% Al2 O3, were prepared by hot-pressing (HP) at 50–60 MPa and sintered at 1300–1350 °C for 1 h. Microstructural features, phase composition and mechanical properties were investigated. The strength was measured by 4-point bending (4P-B), piston-on-three-balls (P-3B) and three-balls-on-three-balls (3B-3B) biaxial methods. Toughness was determined by indentation strength in bending (ISB). Vickers hardness (Hv) and the Young modulus (E) were also estimated. Preliminary aging behaviour (LTD) was also here considered. Measured biaxial strength was significantly higher (until 1.83 times) than the uniaxial one because of the tetragonal to monoclinic (t-m) zirconia phase transformation which is strongly influenced by the loading configuration. The variation of the strength with the testing method is attributed to the compressive stresses generated by the phase transformation which is particularly favoured under P-3B tests and also to the calculation of the stresses from elastic theories. LTD preliminary tests showed excellent aging resistance of 3Yb-0.5A ceramics.